2015
DOI: 10.1002/stem.2072
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin Promotes Hepatic Progenitor Cell Expansion and Tumorigenicity via Activation of β-Catenin in Mice

Abstract: Upregulation of osteopontin (OPN) has been found in hepatic progenitor cells (HPCs) in several liver diseases with portal biliary proliferation. Here, we investigated the role of HPC-derived autocrine OPN in regulating HPC expansion, migration, and hepatocarcinogenesis in mice. Fiveweek-old, weighing between 18 and 20 g of either wild type (WT) or OPN gene knockout (OPN-KO) male mice were treated with modified choline-deficient, ethionine-supplemented diet (modified choline-deficient [MCDE]) for 2 weeks to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
(51 reference statements)
1
21
0
1
Order By: Relevance
“…In accord with previous studies, 8, 16 sOPN induced EMT in cancer; whereas the nuclear OPN triggered MET through the AKT1/miR-429/ZEB axis through interaction with HIF2 α . In vivo studies and patient samples further supported the diverse roles of sOPN and iOPN in tumor metastasis.…”
supporting
confidence: 92%
“…In accord with previous studies, 8, 16 sOPN induced EMT in cancer; whereas the nuclear OPN triggered MET through the AKT1/miR-429/ZEB axis through interaction with HIF2 α . In vivo studies and patient samples further supported the diverse roles of sOPN and iOPN in tumor metastasis.…”
supporting
confidence: 92%
“…Previous studies have shown that OPN works by binding to cell surface receptors [28], and integrin αν / β 1 and CD44 are indeed highly expressed on MSCs [29]. We then used specific antibodies against the OPN receptors to determine which receptors mediate the effect of OPN on ASC differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…HpSCs can activate stellate/endothelial cells via the Hedgehog (Hh) pathway resulting in release of types of matrix components (e.g., type IV collagen, laminin, syndecans, and glypicans) associated with normal liver regeneration [ 70 , 73 , 86 ]; other key paracrine signals include OPN and transforming growth factor- β 1 (TGF- β 1) which induce collagen-I deposition and other matrix components associated with fibrosis by stellate cells and MFs [ 87 , 88 ]. The OPN synthesized by HpSCs could also have an autocrine role in HpSC expansion and migration (via disruption of cell adhesion) [ 89 ]. In chronic pathological conditions, this cellular cross-talk of paracrine signals could be responsible in establishing a profibrogenic loop [ 57 ]; in fibrogenesis, MF activation is secondary to the expansion of the HpSC compartment mediated in part by the Hh pathway [ 90 ] along with signaling pathways induced by chronic injury [ 77 ].…”
Section: Hpsc Activation Is Driven By a Specialized Nichementioning
confidence: 99%